Luxembourg : Financial System Stability Assessment; Update. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
Luxembourg hosts a large international financial center that plays a pivotal role in its economy and in European financial markets. The crisis exposed significant vulnerabilities in Luxembourg's financial system, owing to large cross-border exposures to foreign parent banks. The authorities proceeded with large public support to systemically important financial institutions under stress and with a fivefold increase in the deposit guarantee. Strengthening home-host supervisory collaboration and cross-border bank resolution frameworks will be of crucial importance for Luxembourg. Financial stability assessment and stress tests are also carried out.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet